Capital-Skill Complementarity and the Emergence of Labor Emancipation - Quamrul H. Ashraf; Francesco Cinnirella; Oded Galor; Boris Gershman; Erik Hornung (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper advances a novel hypothesis regarding the historical roots of labor emancipation. It argues that the decline of coercive labor institutions in the industrial phase of development has been an inevitable by-product of the intensification of capital-skill complementarity in the production process. In light of the growing significance of skilled labor for fostering the return to physical capital, elites in society were induced to relinquish their historically profitable coercion of labor in favor of employing free skilled workers, thereby incentivizing the masses to engage in broad-based human capital acquisition, without fear of losing their skill premium to expropriation. In line with the proposed hypothesis, exploiting a plausibly exogenous source of variation in early industrialization across regions of nineteenth-century Prussia, capital abundance is shown to have contributed to the subsequent intensity of de facto serf emancipation.
Keywords: J24; J47; N13; N33; O14; O15; O43; 330; labor coercion; serfdom; emancipation; industrialization; physical capital accumulation; capital-skill complementarity; demand for human capital; nineteenth-century Prussia